Unmet Needs of Individuals With Acute Traumatic Eye Injury. (March 2022) - Gerolamo, Angela M.; Gentsch, Alexzandra; Alexander, Rachel; Paglia, Helen; Schlegel, Lauren; Rising, Kristin L.
Introduction: Although traumatic eye injuries can have a far-reaching impact on an individual and society, traumatic eye injury has not been a focus of research. The purpose of this study is to examine individuals' experiences after traumatic vision loss and identify their needs.Methods: We used a qualitative approach to conduct semi-structured interviews with individuals who experienced traumatic vision loss and were treated at a specialty eye hospital in an urban setting. Participants also completed a demographic survey and the National Eye Institute Visual Functioning Questionnaire–25 (VFQ-25). Content analysis was used to analyze qualitative data and descriptive statistics were used to summarize quantitative data.Results: Interviews with 26 participants resulted in three categories of patient needs: informational, functional, and psychosocial. Participants wanted more information from providers about what to expect over time and identified driving as a significant challenge that affected their daily lives. Participants offered suggestions for addressing their functional needs including assistance with transportation to appointments, physical therapy, and occupational therapy. Participants also discussed how vision loss affected their livelihood and finances, with a subset of participants experiencing significant mental health distress. Some participants suggested that a recovery coach, peer support, support groups, and mental health services would be beneficial for addressing their psychosocial needs.Discussion: Our findings point to a significant gap in services available to meet the needs of individuals with traumatic eye injuries. Future research is needed to test the effect of an integrated-care model that includes routine offering of psychosocial and functional services for patients with acute vision loss to determine the effect on outcomes.Implications for Practitioners: This work has far-reaching implications for providers, since it supports the need for the development and delivery of integrated interventions that emphasize addressing psychosocial and functional aspects of recovery.